9th report on carcinogens. (U.S. Dept. of Health and Human Services, Public Health Service, National Toxicology Program, 2001)
This document was first ordered by Congress in 1978 to educate both the public and health professionals in the recognition that many cancers are apparently induced by chemicals in the home, workplace, general environment, and from the use of certain drugs.
Title from title page of source document.
"Pursuant to Section 301(b) (4) of the Public Health Service Act as Amended by Section 262, PL 95-622."
Keywords: Carcinogens.; Toxicology.; elektronické knihy; electronic books